File Upload Security: Essential Practices for Programmers - Anrie Suryaningrat; Desi Ramayanti; Glen Maxi Taberima; Panji Pratama Kurniawan (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
File upload processes, while convenient, introduce data security risks that must be addressed. Potential malware infections, sensitive information leaks, and data corruption necessitate the implementation of effective strategies and solutions. Data integrity refers to the accuracy, consistency, and reliability of stored and processed data. Human error, system failures, and cyberattacks can compromise data integrity, necessitating effective preventive and mitigation measures. Data security and file upload integrity are critical aspects of modern web applications. Given the escalating cyber threat landscape, implementing best practices to safeguard user data and ensure the authenticity of uploaded files is paramount. This paper delves into the implementation of best practices for protecting user data and ensuring file upload authenticity. The study proposes the implementation of best practices for secure file upload mechanisms in web applications, including the innovative application of hash-salting techniques. By adhering to the guidelines presented, developers can bolster the defenses of their web applications against a wide range of cyber threats, enhance user trust, and protect sensitive data. This approach also serves as an effective solution for improving efficiency, security, and compliance in digital records management.